Monday

September 22, 2014

September 22, 2014

Posted by **Anonymous** on Tuesday, January 29, 2013 at 7:32am.

using first principle method.

- maths -
**Reiny**, Tuesday, January 29, 2013 at 8:19amyou meant:

f(x) = y = (2x+3)/(3x-2)

so f(x+h) = (2x + 2h + 3)/(3x + 3h - 2)

dy/dx = lim [ (2x+2h+3)/(3x+3h-2) - (2x+3)/(3x-2) ]/h , as h --->0

= lim [ ((2x + 2h + 3)(3x-2) - (2x+3)(3x+3h+2))/((3x+3h-2)(3x+h))]/h

= lim [ (5h/((3x+3h-2)(3x-2))]/h , as h -->0

= lim 5/((3x+3h-2)(3x-2)) , as h -->0

= 5/(3x-2)^2

**Answer this Question**

**Related Questions**

Applied Calculus - Find the first and second derivative of the function: x/(7x+...

math - find the local maximum and minimum values of f using both the first and ...

calculus - find the local maximum and minimum values of f using both the first ...

maths - Find dy/dx of the function f(x) =1/x from first principle

Calculus - derivatives - Okay, I want to find the derivative of (x^x)^(x^x)... ...

calculus - Find the first and second derivative - simplify your answer. y=x/4x+1...

calculus - Given y^4 -x^4=16 find and simplify d2y/dx2 using implicit ...

calc - derivative of (x^3/6)+(1/2x)? i got (x^2/2)-(1/2x^2) is that correct? and...

Maths - Pigeon-hole principle - Using the Pigeon-hole principle... 91 five-digit...

Maths Calculus - Find the first derivative for the following functions 1) x^3 . ...